O PROGRAMA NACIONAL DE ACESSO AO ENSINO TÉCNICO E AO EMPREGO E A CONCEPÇÃO DE EDUCAÇÃO PROFISSIONAL NA BASE NORMATIVA E NA OBJETIVAÇÃO DA BOLSA-FORMAÇÃO NUMA EXPERIÊNCIA INSTITUCIONAL - Matos, Francilene do Rosário de (2015)
The research deals with ""The National Programme for Access to Technical Education and Employment (Pronatec) and the conception of vocational and technological education in basic standards and objectification of bag-training an institutional experience" " in an effort to understand the meaning of the Professional Education, while Brazilian public policy in the context of productive restructuring capitalism. It has links with the research group Policy and Basic Education, State and Educational Management research line of the Post-Graduate Education, Federal University of Maranhão. The methodology is oriented on historical dialectic materialism and uses literature, document analysis and descriptive study. Among the referenced authors are: Braverman, Castells Chesnais, Coriat, Franco, Friedmann, Frigotto, Harvey, Kuenzer, Milk, Lopes, Axe, Manacorda, Marx, Netto, Paiva, Ramos, Saviani, Zarifian, Anderson, Araújo Batista, Cabral Neto, Cardozo, Carnoy, Cunha, Daros, Gold, Fagnani, Gohn, Haddad, Manfredi, Sousa, Rodrigues, Tauile, Veiga, Yanaguita, among others. His argumentative text systematized into four sections, the first being reserved for the demarcation of the object, the methodological approach and the text organization. The second part analyzes the relationship between productive restructuring, work organization and professional qualification. In the third, is a brief history of EFA policies, since the second half of the twentieth century. And, in the fourth section are the data and analysis on the design of EPT Pronatec expressed in the normative basis of the Exchange Training and its objectification in a public institution. The results showed the relationship of design EPT Pronatec to the Brazilian educational reform and the CLAIMS of organized society. Proved instrumental character of the program, supporting economic growth and social control, without any commitment to confronting the hegemonic ideology or overcoming social inequality. The EPT is designed to meet the demands of the market, ensuring the diversity of skill levels of the workforce. The resolutions, implementation and evaluation of the program are alien to the active participation of society. Thus, the design of EPT Pronatec does not break with the historical duality between manual and intellectual work, however, ratified the educational functionality, a fragile conjunction with high school and a disconnect between initial training and technical training.